CLINICAL-EPIDEMIOLOGICAL PROFILE OF DENGUE IN THE MUNICIPALITY OF ANÁPOLIS - GOIÁS FROM 2016 TO 2020 - Teixeira, Larissa Schults; Mota, Mariana Santos; Oliveira, Núrya Patielly Teixeira; Negreiros, Camila Beraldo; Silva, Bruna Mendonça; Correia, Sara Fernandes; Silva, Constanza Thaise Xavier (Cogitare Enfermagem, 2022)
Objective: to describe the clinical epidemiological profile of dengue in Anápolis, Goiás - BR between the years 2016 to 2020. Methods: descriptive study of a quantitative nature. Data from the dengue notification form registered in the Epidemiological Surveillance Department were used. Chi-square test was used with significance level five (5%) (p<0.05). Results: 27,544 cases were notified with the peak in 2019, being 54.2% female, age group 25 to 44 years 36.7% and brown color 70.3%. Of the cases that occurred, 97.7% were not hospitalized, classic dengue predominated in 98% and cure was obtained in 99.9% of cases. There was a significant difference regarding age group and dengue classification, hospitalization, and clinical evolution (p= 0.001). Conclusion: It is evident that dengue is prevalent in Anápolis, and strategies of prevention and control of the vector are necessary, especially during seasonal periods.